2004
DOI: 10.1007/s00213-004-1783-0
|View full text |Cite
|
Sign up to set email alerts
|

Intraseptal injection of the 5-HT1A/5-HT7 agonist 8-OH-DPAT and working memory in rats

Abstract: These results extend those of a previous experiment which showed that intraseptal injections of 8-OH-DPAT impaired spatial reference memory. Based on the characteristics of the observed deficits, it is suggested that the 8-OH-DPAT-induced impairment, rather than being only the result of a true alteration of working memory, might reflect a more global cognitive deficiency in which alteration of general memory capacities may be biased by disrupted search strategies/exploration and/or dysfunctions of attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 58 publications
2
19
1
Order By: Relevance
“…Working memory procedure: During nine other consecutive days, the platform was placed in a new location each day, and the rats were released from each of two starting points on two consecutive trials separated by 10 s. The platform locations were those described by Jeltsch et al (2004a).…”
Section: Behavioral Testingmentioning
confidence: 99%
“…Working memory procedure: During nine other consecutive days, the platform was placed in a new location each day, and the rats were released from each of two starting points on two consecutive trials separated by 10 s. The platform locations were those described by Jeltsch et al (2004a).…”
Section: Behavioral Testingmentioning
confidence: 99%
“…on day 5. This indicates that their results probably relates to effects on working or short-term memory functions, which has shown to be impaired by intraseptal injections of 8-OH-DPAT (0.5 and 4 lg) (Jeltsch et al, 2004). In view of the short retention time used by Bertrand et al (2000), it seems likely that 8-OH-DPAT is still bound to brain 5-HT 1A receptors during retention testing, since the half-life of 8-OH-DPAT in the rat brain is 40 min (Yu and Lewander, 1997).…”
Section: Discussionmentioning
confidence: 92%
“…The present experiment was conducted with the more active enantiomer, (R)-(1)-8-hydroxy-2-(di-npropylamino)tertralin hydrobromide ((R)-8-OH-DPAT) (SigmaAldrich, Stockholm, Sweden), which, unlike the racemic form, is a full agonist at the 5-HT 1A receptor (Cornfield et al, 1991). The doses of (R)-8-OH-DPAT (1 and 4 lg) were based on earlier studies in the rat where intraseptal infusions of 8-OH-DPAT (4 lg) was reported to impair water maze performance (Bertrand et al, 2000;Jeltsch et al, 2004;Koenig et al, 2008). D-(2)-2-amino-5-phosphonopentanoic acid (D-AP5) (Tocris, Bromma, Sweden) is the active enantiomer of AP5 and a competitive antagonist on the glutamatergic NMDA receptors (Davies and Watkins, 1982).…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the passive avoidance test was used here and in other studies [43,45,47,50,51] as a simple learning and memory task, other studies have used it as an index of attentional and emotional factors [9,20,36,40].…”
Section: Behavioral Testingmentioning
confidence: 99%